2010
DOI: 10.1016/j.bjmsu.2009.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Do We Need Chaperones for Intimate Examination in Urology Clinics? Patients' Preferences and Urologists' Practice in Scotland

Abstract: Introduction: General Medical Council (GMC) guidelines and the Ayling report recommend that a chaperone should be offered to all patients for every intimate examination. We wanted to establish whether these guidelines reflect men's preferences and urologists' current practice in intimate examination. Methods: All male patients attending urology outpatient clinics over a 3 month period at two hospitals were asked to fill in a preference questionnaire. A separate questionnaire was sent to all urologists in Scotl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…In an earlier study, the majority (73%) of male urology patients felt a chaperone should be offered for every encounter while a smaller group (14%) actually prefer a chaperone to be present. 9 A later study confirmed this finding, revealing that the vast majority of urology patients, both men and women, believe that chaperones should be offered and that urological patients have the right to refuse a chaperone. 8 The offer of a chaperone on its own is seen as a sign of respect for the patient in that chaperone-use becomes a patientcentered healthcare decision.…”
Section: Perspectives On Chaperonesmentioning
confidence: 84%
See 3 more Smart Citations
“…In an earlier study, the majority (73%) of male urology patients felt a chaperone should be offered for every encounter while a smaller group (14%) actually prefer a chaperone to be present. 9 A later study confirmed this finding, revealing that the vast majority of urology patients, both men and women, believe that chaperones should be offered and that urological patients have the right to refuse a chaperone. 8 The offer of a chaperone on its own is seen as a sign of respect for the patient in that chaperone-use becomes a patientcentered healthcare decision.…”
Section: Perspectives On Chaperonesmentioning
confidence: 84%
“…7 Other studies within urology established that most patients did not care about gender of the chaperone, focusing more on comfortability with their provider and invasiveness of the procedure. 8,9 Patients' preference for a chaperone was not influenced by the gender or profession of the examiner. 9 Another key finding is that the majority of patients prefer a chaperone to be either their family member or their friend.…”
Section: Perspectives On Chaperonesmentioning
confidence: 94%
See 2 more Smart Citations
“…A search of the published literature worldwide found limited research about the use of chaperones overseas whether in primary care [ 5 , 12 , 14 , 15 ] or hospital clinics [ 6 , 16 19 ] about patients' awareness [ 13 , 17 , 20 ], protection for patients and/or doctors [ 3 , 11 , 21 ], or guidelines [ 22 – 24 ]. Similarly, little literature was found about the use of chaperones in Australia; results of two studies conducted in sexual health clinics [ 4 , 25 , 26 ], commentaries about doctors' misconduct [ 1 ], and risk management [ 27 ], as well as three documents providing medicolegal guidance [ 7 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%